The Relationship between Metabolic Control and Growth in Children with Type I Diabetes Mellitus in Southwest of Iran - Shide Assar; Koroush Riahi; Shiva Bashirnezhad; Leila Yazdanpanah; Seyed Mahmoud Latifi (Scientifica)
Background. Metabolic control is an important factor in growth of children with type I diabetes. This study assessed the relationship between growth and metabolic control in such children. Materials and Methods. 83 children with diabetes were studied. They were examined for weight and height gain and HbA1C was quantified every 3 months for one year. The growth process was studied in patients who were divided into 3 groups according to their HbA1C amounts, consisting of good, intermediate, and poor metabolic control. Results. Mean age of cases was 7.6 ± 2. The presenting sign at the onset of disease was diabetic ketoacidosis in 44.6%. The average HbA1C amount was 8.89%. The average weight SDS at diagnosis was −0.18 and at the end of the study was 0.45 (P<0.001). The average height SDS at diagnosis was −0.04 and at the end of the study was −0.07 (P=0.64). A significant difference in weight SDS changes was only seen between patients with good and poor metabolic control (P=0.04). Conclusion. Poor metabolic control can decrease height growth but has minimal influence on weight. Metabolic control was not the only predictive factor of physical growth in children with diabetes.